Employed and unemployed job seekers: Are they substitutes? - Simonetta Longhi; Mark Taylor (Institute for the Study of Labor (IZA), 2011)
The job search literature suggests that on-the-job search reduces the probability of unemployed people finding a job. However, there is no evidence that employed and unemployed job seekers are similar or apply for the same jobs. We combine the Labour Force Survey and the British Household Panel Survey to compare employed and unemployed job seekers in terms of individual characteristics, preferences over working hours, job-search strategies, and employment histories. We find substantial differences, which persist over the business cycle and remain after controlling for unobserved heterogeneity. We conclude that the unemployed do not directly compete with employed job seekers.
urn:nbn:de:101:1-201107133404
Keywords: J29; J60; 330; on-the-job search; unemployment; job competition; employment histories; panel data